Advantages of Bim Technology in Urban Design - o‘g‘li, Xusainov Sarvarxon Muxammadalixon (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
BIM technology, or Building Information Modeling, is a powerful tool for designing all aspects of a building. Urban design based on BIM technology enables comprehensive and collaborative planning, design, construction and management of entire cities. With BIM, city planners can create detailed 3D models of streets, buildings, utility systems, and other critical infrastructure elements. This modeling allows city officials to assess potential problems and make adjustments before construction begins. BIM also helps streamline communication between multiple parties involved in urban construction, resulting in more effective teamwork and ultimately better cities.